2017
DOI: 10.2341/15-335-c
|View full text |Cite
|
Sign up to set email alerts
|

Longevity, Esthetic Perception, and Psychosocial Impact of Teeth Bleaching by Low (6%) Hydrogen Peroxide Concentration for In-office Treatment: A Randomized Clinical Trial

Abstract: The two compounds remained effective at nine months, with a slight rebound of color, and maintained their objective color difference but not the subjective color difference. Patients were satisfied with the bleaching procedure, and this had a positive impact on esthetic perception and a positive psychosocial impact at the nine-month recall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 38 publications
3
49
1
4
Order By: Relevance
“…The results based on the Δ L , Δ a , and Δ b were very similar except in a preprophylaxis period that was explained by stains mainly affecting the luminosity of color of both groups. Recent trials showed that the color had a slight change during prophylaxis; this concurs with our results …”
Section: Discussionmentioning
confidence: 99%
“…The results based on the Δ L , Δ a , and Δ b were very similar except in a preprophylaxis period that was explained by stains mainly affecting the luminosity of color of both groups. Recent trials showed that the color had a slight change during prophylaxis; this concurs with our results …”
Section: Discussionmentioning
confidence: 99%
“…3,4,5,6 Researchers have used clinical or in vitro studies to obtain data that can Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a bleaching agent with concentration even lower, 6% hydrogen peroxide containing TiO_N nanoparticles, has been studied [4,31,32]. Martin et al (23) evaluated the efficacy of this new bleaching agent with 6% of hydrogen peroxide containing TiO_N [24]. They showed a reductionof the tooth sensitivity intensity and a clinically insignificant lower effectiveness a 35% hydrogen peroxide agent.…”
mentioning
confidence: 99%
“…Regarding the effect on the aesthetic perception and psychosocial impact, there are some reports of Martin et al [4] and Fernandez et al [24] showing a positive effect on these two areas, topics that you should be much more investigation in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation